G337(P) Metal detection in the paediatric emergency department (MEDIPED): a PERUKI study. (May 2019) - Lafferty, M; Mullen, N; Lyttle, M
Abstract : Aims: Ingested metallic foreign bodies (FBs) are a common reason for children to present to Paediatric Emergency Departments (PEDs). Hand-held metal detectors (HHMDs) are reported to be highly sensitive for identifying and localizing metallic FBs. However little is known about how PEDs use HHMDs and no standardised guidelines exist. This study aimed to determine how many PEDs use HHMDs, how they aid clinical decision making, and what training is given in their use. Methods: Between 19/03/2018 and 03/05/2018 we conducted an online survey via Paediatric Emergency Research in the UK and Ireland (PERUKI), an international PEM research collaborative. One participant was invited from each site; participants were asked to complete the survey (which contained questions on site practice and training) and submitted their local guideline where available. Results are presented using descriptive statistics. Results: 55/61 (90%) sites responded. 30/55 (55%) used HHMDs, of which 21/30 (70%) had guidelines for their use and 3/30 (10%) provided formal training. 20/30 (67%) used the xiphisternum as the anatomical cut-off for assuming safe FB passage. 16/30 (53%) scanned from neck to pelvis anteriorly and posteriorly in the midline and laterally, 9/30 (30%) scanned anteriorly only, and 5/30 (17%) scanned posteriorly in the midline only. 17/30 (57%) restricted use based on patient characteristics including obesity and age (adolescence). 21/30 (70%) allow discharge from PED if a FB is confirmed by a HHMD to be absent. 27 (90%) allow discharge from PED if a HHMD identifies it below an anatomical cut-off. 18/30 (60%) used HHMDs at triage, of which 6/18 (34%) allow immediate discharge if FB is absent, or identified below an anatomical landmark. Conclusion: More than half of PEDs in the UK and Ireland use HHMDs to identify metallic FBs in children. Usage may not be universal because of concerns that HHMDs are not registered medical devices. Nevertheless there is little formal training in their use and large variation in practice in how they are used in clinical decision making. We propose a standardised guideline and training package for the use of HHMDs.